CASE STUDY OF INTEGRATED INTERPRETATION FROM WELL CTW-01 IN CHARACTERIZING KATI FORMATION AT SERI ISKANDAR, PERAK - SAHARI, SUFIZIKRI (2019)
Many studies have been conducted in Kati Formation, however none yet had covered the subsurface studies of the formation through well analysis, especially in Seri Iskandar area. The previous study only covered the surface study of Kati Formation in Seri Iskandar area, thus this study will fill the gap of subsurface study area. Thus, the research focuses on integrating well log analysis and core analysis from well CTW-01 to characterize the Kati formation particularly in Seri Iskandar, Perak to evaluate its potential to be a reservoir rock. The study objectives in order to characterize the formation areto quantitatively analyse the rock physical properties of the Kati formation in Seri Iskandar followed by synthetic logs modelling, facies characterization and identification of its potential paleo-depositional environment.